Formation of the Economic Model and the Impact of Economic Factors on the Health of Russian Population - ROMANOVA, Tamara G.; BATOMUNKUEVA, Valentina D.; GYRGENOVA, Tatiana K.; MONGOLOVA, Nataliya V.; TSYDYPOV, Roman Zh. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).28, 2018)
The article is about the influence of economic factors on the health quality of the population as a public benefit. Health of the individual has an important role in national economy, both in processes of formation of public health, and in reproduction of quality of a manpower. The review of the indicators of evaluation test of health of the population applied in the Russian practice is given in article. Health of the population and economy of the state have close interrelation and interdependence: not only the economy influences health of the population, but also health of the population affects the economy of the state. The technique allowing to assess economic damages from loss of health on the basis of which economic losses from mortality of the population at working-age in Siberian Federal District are estimated is presented. The economic three-level model of health upgrading of the population allows to reveal paths of health upgrading for improvement of economy in the country is developed. The three-level model reflects preventive character with obligatory selection of the measures accompanying achievement of the main task – to upgrade the population health as the public benefit and to increase the level of economy.